Parallel fuzzy control: a self-learning control method with virtual-real interaction and mutual enhancement - Dewang CHEN; Jixiang OU (智能科学与技术学报)
Fuzzy control has advantages such as interpretability and ease of implementation.However, it is limited by its weak self-learning capability, which makes it difficult to effectively utilize the large amount of data accumulated in the control process.Parallel control is a new intelligent control method that enables intelligent control with virtual-real interaction and mutual enhancement, effectively using the Internet and big data to achieve intelligent control.Fuzzy control and parallel control were combined as a new method, and the definition and framework of parallel fuzzy control were proposed and its possible applications were discussed.Parallel fuzzy control has the potential to extend the development direction of fuzzy control and become a new thinking for parallel control.It can effectively utilize big data and some machine learning algorithms based on data-driven to achieve self-learning control, while ensuring interpretability and credibility.